18F-fluorodeoxyglucose positron emission/computed tomography and computed tomography angiography in prosthetic heart valve endocarditis: from guidelines to clinical practice. (16th January 2018) - Swart, Laurens E; Scholtens, Asbjørn M; Tanis, Wilco; Nieman, Koen; Bogers, Ad J J C; Verzijlbergen, Fred J; Krestin, Gabriel P; Roos-Hesselink, Jolien W; Budde, Ricardo P J
Abstract: The timely diagnosis of prosthetic heart valve endocarditis remains challenging yet of utmost importance. 18 F-fluorodeoxyglucose ( 18  F-FDG) positron emission/computed tomography (PET/CT) and cardiac computed tomography angiography (CTA) were recently introduced as additional diagnostic tools in the most recent ESC guidelines on infective endocarditis. However, how to interpret PET/CT findings with regard to what is to be considered abnormal, what the potential confounders may be, as well as which patients benefit most from these additional imaging techniques and how to best perform them in these often-complex patients, remains unclear. This review focusses on factors regarding patient selection and image acquisition that need to be taken into account when employing 18 F-FDG PET/CT and CTA in daily clinical practice, and the importance of a multidisciplinary Endocarditis Team herein. Furthermore, it emphasizes the need for standardized acquisition protocols and image interpretation, especially now that these techniques are starting to be widely embraced by the cardiovascular society.